Synthesis of Vitamin K-Dependent Proteins by Cultured Human Tumor Cells - Al-Mondhiry, Hamid; Wallin, Reidar (Thrombosis and Haemostasis, 1989)
The observation that warfarin inhibits the growth and metastasis of certain types of clinical and experimental tumors suggests a role for vitamin K in tumor biology. We have investigated synthesis of vitamin K-dependent proteins in four malignant (lung epidermoid carcinoma, melanoma, colon adenocarcinoma, and breast adenocarcinoma) and three normal (colon epithelium, breast epithelium, and fibroblasts) cell lines of human origin grown in tissue cultures. Our results show the following: 1) Vitamin K-dependent carboxylase activity is present in all of the malignant and normal cell lines studied. 2) The malignant as well as normal cell lines synthesize a family of vitamin K-dependent proteins. Microsomal precursors of these proteins with apparent molecular mass of 74, 62, and 34 kDa are common to all malignant and normal cell lines whereas precursors of higher and lower molecular mass seem to be synthesized by some but not all tumor cell lines. 3) The 74 kDa precursor synthesized by colon carcinoma and breast carcinoma was positively identified as a precursor of protein S.
Keywords: Vitamin K; Human cancer; Clotting factors; Tumorprocoagulant